Detection of anti-Toxoplasma gondii antibodies in experimentally and naturally infected non-human primates by Indirect Fluorescence Assay (IFA) and indirect ELISA - Bouer, Andréa [UNESP]; Werther, Karin [UNESP]; Machado, Rosangela Zacarias [UNESP]; Nakaghi, Andréa Cristina Higa [UNESP]; Epiphanio, Sabrina; Catão-Dias, José Luiz (FapUNIFESP (SciELO), 2010)
The Indirect Fluorescence Assay (IFA) and the indirect ELISA were comparatively used to detect IgG and IgM antibodies for Toxoplasma gondii in experimentally and naturally infected primates. In the experimentally infected group, antibodies of diagnostic value were detected at day 9 post-infection (PI) with the IFA (IgG and IgM) and with IgG-ELISA. IgM-ELISA detected antibodies for T. gondii starting at day 3 PI until the end of the experiment (102 days PI). Of the 209 naturally infected sera tested, from many zoos of State of Sao Paulo, 64.59 and 67.94% were positive in the IgG-IFA test and IgG-ELISA respectively. IgM-ELISA test detected seropositivity in 52.63% of the sera although IgM-IFA test detected it in only in 0.96% of the samples. The differential toxoplasmosis diagnosis was accomplished with Neospora caninum by IFA, observing 61 (29.2%) seropositive animals for this parasite and 149 (70.8%) negative. Sixty animals were positive for both T. gondii and N. caninum. Pneumonia, splenomegaly, and intestinal ulcers were macroscopically observed. Unremarkable interstitial pneumonia, enteritis, colitis, splenitis, and glomerulitis were microscopically observed. The immunohistochemical stain could not detect the presence of T. gondii in the tissues of the animals infected experimentally.
Detecção de anticorpos anti-Toxoplasma gondii por meio das técnicas de Imunofluorescência Indireta e ELISA indireto em primatas experimentalmente e naturalmente infectados
Keywords: ELISA; Indirect Fluorescence Assay; Primates; Toxoplasma gondii; Toxoplasmosis